Internet gaming disorder : theory, assessment, treatment, and prevention - King, Daniel L.; Delfabbro, Paul H. (Paul Howard) (Academic Press, an imprint of Elsevier, 2019)
Internet Gaming Disorder: Theory, Assessment, Treatment, and Prevention is an informative and practical introduction to the topics of Internet gaming disorder and problematic gaming. This book provides mental health clinicians with hands-on assessment, prevention, and treatment techniques for clients with problematic gaming behaviors and Internet gaming disorder. It provides an overview of the existing research on epidemiology, risk and protective factors, and discusses the distinct cognitive features that distinguish gaming from gambling and other related activities and disorders. Clinicians will find interest in discussion of the latest developments in cognitive-behavioral approaches to gaming disorder as well as the best structure for clinical interviews. Included in clinical sections are details of the key indicators of harm and impairment associated with problem gaming and how these might present in clinical cases. Internet Gaming Disorder is strongly evidence-based, draws extensively upon the latest international research literature, and provides insights into the likely future developments in this emerging field both in terms of technological development and new research approaches.